Komposisi dan struktur vegetasi lahan pertanian di sekitar kawasan wisata alam Candi Gedong Songo, Kabupaten Semarang, Jawa Tengah - Arief Budiman; Jumari Jumari; Lilih Khotimperwati (Jurnal Biologi Tropika, 2020)
There is agricultural land around the Semarang Gedong Songo Temple area. The existence of land adjacent to tourist sites, how to manage land and the insistence of various interests may affect the condition of existing land and vegetation. The purpose of this study is to examine the composition of vegetation and vegetation structure, on agricultural land around the tourist area of Gedong Songo Temple. Sampling uses a quadratic plot with a line transect. Sampling was carried out on 3 strata, trees 10m x 10m, shrubs 5m x 5m, and herbs 1m x 1m. Data collection was carried out on sample plots, vegetation structures were assessed based on density, frequency and dominance values. Important value index (IVI ) is obtained from the sum of the values of relative density, relative frequency and relative dominance. The results showed 2 types of trees, 5 types of shrubs and 11 types of herbs, most of the herbs are weeds. Horticultural plants tend to be dominant (high IVI) due to human cultivation factors. The total IVI of horticultural crops is lower than that of weeds.